2000
DOI: 10.1046/j.1471-4159.2000.0750812.x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Cortical Spreading Depression Decreases Intraischemic Cerebral Glutamate Levels and Down‐Regulates Excitatory Amino Acid Transporters EAAT1 and EAAT2 from Rat Cerebal Cortex Plasma Membranes

Abstract: Abstract:We previously reported a 50% reduction in cortical infarct volume following transient focal cerebral ischemia in rats preconditioned 3 days earlier with cortical spreading depression (CSD). The mechanism of the protective effect of prior CSD remains unknown. Recent studies demonstrate reversal of excitatory amino acid transporters (EAATs) to be a principal cause for elevated extracellular glutamate levels during cerebral ischemia. The present study measured the effect of CSD preconditioning on (a) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Because normobaric hypoxia (9% O 2 , 8 hours) has been reported to induce tolerance against kainate-induced seizures (Pohle and Rauca, 1994), one might suppose that the mechanisms of hypoxic preconditioning involve a reduction of the excitotoxic events during focal ischemia. Such a hypothesis has already been suggested for other models of ischemic tolerance (Douen et al, 2000). Although we did not investigate these hypotheses, we cannot exclude a potential implication of these signaling pathways in the development of ischemic tolerance.…”
Section: Bernaudin Et Al 398mentioning
confidence: 69%
“…Because normobaric hypoxia (9% O 2 , 8 hours) has been reported to induce tolerance against kainate-induced seizures (Pohle and Rauca, 1994), one might suppose that the mechanisms of hypoxic preconditioning involve a reduction of the excitotoxic events during focal ischemia. Such a hypothesis has already been suggested for other models of ischemic tolerance (Douen et al, 2000). Although we did not investigate these hypotheses, we cannot exclude a potential implication of these signaling pathways in the development of ischemic tolerance.…”
Section: Bernaudin Et Al 398mentioning
confidence: 69%
“…Although numerous studies have reported increased tolerance to ischemia following preconditioning of the mammalian brain with OGD, cortical spreading depression (CSD), or middle cerebral artery occlusion (MCAO), the mechanism underlying this neuroprotection is unclear (17)(18)(19)(20). Some studies have reported that neurons themselves acquire resistance against ischemia through preconditioning (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies including by us have reported increased tolerance to ischemia following preconditioning of the mammalian brain with OGD, cortical spreading depression (CSD), or middle cerebral artery occlusion (MCAO), the mechanism underlying this neuroprotection is unclear (20)(21)(22)(23). Some studies have reported that neurons themselves acquire tolerance against ischemia through preconditioning (22, 23).…”
Section: Discussionmentioning
confidence: 99%